Association of usual 24-h sodium excretion with measures of adiposity among adults in the United States: NHANES, 2014. Issue 1 (8th January 2019) - Zhao, Lixia; Cogswell, Mary E; Yang, Quanhe; Zhang, Zefeng; Onufrak, Stephen; Jackson, Sandra L; Chen, Te-Ching; Loria, Catherine M; Wang, Chia-Yih; Wright, Jacqueline D; Terry, Ana L; Merritt, Robert; et al.
ABSTRACT: Background: Both excessive sodium intake and obesity are risk factors for hypertension and cardiovascular disease. The association between sodium intake and obesity is unclear, with few studies assessing sodium intake using 24-h urine collection. Objectives: Our objective was to assess the association between usual 24-h sodium excretion and measures of adiposity among US adults. Methods: Cross-sectional data were analyzed from a sample of 730 nonpregnant participants aged 20–69 y who provided up to 2 complete 24-h urine specimens in the NHANES 2014 and had data on overweight or obesity [body mass index (kg/m 2 ) ≥25] and central adiposity [waist circumference (WC): >88 cm for women, >102 cm for men]. Measurement error models were used to estimate usual sodium excretion, and multiple linear and logistic regression models were used to assess its associations with measures of adiposity, adjusting for sociodemographic, health, and dietary variables [i.e., energy intake or sugar-sweetened beverage (SSB) intake]. All analyses accounted for the complex survey sample design. Results: Unadjusted mean ± SE usual sodium excretion was 3727 ± 43.5 mg/d and 3145 ± 55.0 mg/d among participants with and without overweight/obesity and 3653 ± 58.1 mg/d and 3443 ± 35.3 mg/d among participants with or without central adiposity, respectively. A 1000-mg/d higher sodium excretion was significantly associated with 3.8-units higher BMI (95% CI: 2.8, 4.8) and a 9.2-cm greater WC (95% CI: 6.9, 11.5 cm) adjusted for covariates. Compared with participants in the lowest quartile of sodium excretion, the adjusted prevalence ratios in the highest quartile were 1.93 (95% CI: 1.69, 2.20) for overweight/obesity and 2.07 (95% CI: 1.74, 2.46) for central adiposity. The associations also were significant when adjusting for SSBs, instead of energy, in models. Conclusions: Higher usual sodium excretion is associated with overweight/obesity and central adiposity among US adults.